Implementation of PPDB Policy for State Middle Schools in Cirebon City - Kadini kadini; Resty Cahyani (International Journal Labs, 2024)
This research examines the implementation of the zoning-based New Student Admissions (PPDB) policy in State Middle Schools in Cirebon City, which is regulated by Minister of Education and Culture Regulation Number 44 of 2019. The aim of this research is to evaluate the effectiveness of zoning policies in equalizing access to education, identify the challenges faced, and provide recommendations for improvement. This research used a qualitative descriptive approach, involving school principals, teachers, students and parents as respondents. The research results show that zoning policies have succeeded in increasing equitable access to education, but face challenges in communication, information consistency and socialization. Recommendations include increased coordination, ongoing training, and intensified outreach to support more effective policy implementation in the future.